The suitability of groundwater in Mosul city for various civilizational uses. - Abdulmoneim Kannah (College of Education for Pure Sciences, 2021)
ABSTRACT : In the current research, 23 wells were chosen from some residential neighborhoods located in the city of Mosul. To study some of the physical properties of well water represented by temperature, electrical conductivity, and total dissolved salts, as well as, the study of chemical analyzes are: (sulfates, chlorides, phosphates, nitrates, sodium, potassium, calcium, magnesium, dissolved oxygen and pH). The results of the study refer to the height of the electrical conductivity, which ranged between (791-2456) µmhos/cm. The results showed that a lot of water is free of dissolved oxygen, as it recorded the highest value of 4.6 mg/l. Whereas, the temperature of the studied water ranged between (20-28.4)Cº, and it is considered warm water. In the current study, the calcium ion concentration was greater than the magnesium ion concentration in all well water, and the highest concentration reached (264 and 134) mg/L at well 22 and 23, respectively. There was an increase in the concentration of chloride ion, which reached (204) mg/L and the lowest concentration (32) mg/l at wells 11 and 7, respectively. When comparing the values of the electrical conductivity of the well water with the global determinants of drinking, it was determined that they are not suitable for drinking. When applying the relationship between the value of the electrical conductivity and the ratio of sodium adsorption to well water, it was found that all water from wells Class (C3 - S1) except for wells (11 and 19) are classified as Class (C4 - S1)